Rapid formation of a stable boron–nitrogen heterocycle in dilute, neutral aqueous solution for bioorthogonal coupling reactions. Issue 95 (8th October 2015) - Dilek, Ozlem; Lei, Zhen; Mukherjee, Kamalika; Bane, Susan
Abstract : Reaction of 2-formylphenylboronic acid with an aromatic hydrazine does not product the expected hydrazone, but rather a boron-containing aromatic heterocycle. The characteristics of the reaction are highly desirable for bioconjugations. Abstract : Combining 2-formylphenylboronic acid with 4-hydrazinylbenzoic acid in neutral aqueous solution at low, equimolar concentrations of the reagents results in a single, stable product, a 1, 2-dihydro-1-hydroxy-2, 3, 1-benzodiazaborine, in a matter of minutes with no side products. Application of this reaction to protein conjugation demonstrates that the reaction is orthogonal to protein functional groups, and the resulting conjugate withstands SDS-PAGE analysis. This reaction should be particularly useful for couplings that must be performed with low concentrations of reagents under physiologically compatible conditions.